A-216 Construct Validity of The National Institutes of Health Toolbox- Cognition Battery (NIHTB-CB) in Children and Adolescents with Cerebral Cavernous Malformation, Type 1 (CCM-1) and their Non-Affected Relatives. (17th August 2022) - Petranovich, Christine; Campbell, Richard; Gill, Darbi; Hart, Blaine; Morrison, Leslie; Wilson, Kevin
Abstract: Objective: This study assessed the convergent validity of the NIHTB-CB in a sample of children and adolescents with CCM-1 and non-affected relatives. Method: Twenty-two participants with CCM-1 and 7 non-affected relatives completed the NIHTB-CB and traditional neuropsychological measures. The following domains were assessed: memory (NIHTB-CB Picture Sequencing Memory and Child and Adolescent Memory Profile- Screening Index), word reading (NIHTB-CB Oral Reading and Wide Range Achievement Test-4th Word Reading [WRAT-4 WR]), processing speed (NIHTB-CB Pattern Comparison and Symbol Digit Modalities Test), and attention/working memory (NIHTB-CB List Sorting and Digit Span). Results: The non-affected group scored higher than the CCM-1 group on WRAT-4 WR (t = 2.68, p = .02) and NIHTB-CB Oral Reading (t = 2.18, p = .05). The groups did not differ on the other measures (p > .05). Pearson's correlations ranged from .45 for memory to .81 for word reading, demonstrating adequate construct validity for memory, processing speed, and attention/ working memory and good to very good for word reading. The NIHTB-CB was more likely to identify participants as impaired for memory (17.2% vs 6.9%) and processing speed (62.1% vs. 3.4%). The traditional attention/working memory measure was more likely to identify participants as impaired (27.6% vs 3.4%). Impairment rates were similar for the word reading measures. Conclusions: Of the domains considered, convergent validity was best established for word reading. Although correlations were adequate, rates of impairment differed for memory, processing speed, and attention/ working memory, suggesting that caution is warranted when comparing the NIHTB-CB to traditional measures in these areas.